2017
DOI: 10.1016/j.ocecoaman.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Realising a vision of no net loss through marine biodiversity offsetting in Australia

Abstract: Biodiversity offsets are increasingly used in policy frameworks to regulate the environmental impacts of development including projects located in marine environments. Scientific knowledge gaps and other practical challenges have necessitated flexibility concerning the manner in which key offsetting principles are implemented in policy frameworks relevant to such environments. The potential tradeoff of such flexibility is that consequent marine offsetting practice may not be compatible with the ultimate object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…These criteria, particularly that of additionality, are designed to ensure that the net balance of biodiversity is only ever measured against the scenario most likely to have occurred in the absence of impact or compensatory intervention (Ferraro and Pattanayak, 2006). The strict application of these criteria, essential to realize an aim of NNL and to avoid offset misuse, have been found to be challenging in marine contexts (UNEP-WCMC, 2016;Niner et al, 2017b).…”
Section: Biodiversity Offsetting In the Deep Seamentioning
confidence: 99%
“…These criteria, particularly that of additionality, are designed to ensure that the net balance of biodiversity is only ever measured against the scenario most likely to have occurred in the absence of impact or compensatory intervention (Ferraro and Pattanayak, 2006). The strict application of these criteria, essential to realize an aim of NNL and to avoid offset misuse, have been found to be challenging in marine contexts (UNEP-WCMC, 2016;Niner et al, 2017b).…”
Section: Biodiversity Offsetting In the Deep Seamentioning
confidence: 99%
“…In order to be considered appropriate, indirect offsets need to provide measurable biodiversity gains (Gardner et al, 2013). As the link between indirect offset activities and measurable biodiversity outcomes is not always clear, regulators usually require direct offsets over indirect offsets (Niner, Milligan, Jones & Styan, 2017). Therefore, this review will focus on direct biodiversity offsets.…”
Section: Type Of Compensatory Measurementioning
confidence: 99%
“…Experiences across the world (Burgin, 2010;Gordon et al, 2015;Kaiser, 2001;Kihslinger, 2008;Maron et al, 2015Maron et al, , 2012Robertson, 2004Robertson, , 2012Santos et al, 2015;Brock, 2015, among others) have shown that the ecological 'success rate' of offsetting was questionable at best. They point to the problems of measurements, accounting methods and lack of fungibility and commensurability of nature (Maron et al, 2015;Niner et al, 2017;Pawliczek and Sullivan, 2011;Robertson, 2004Robertson, , 2012Sullivan and Hannis, 2015). Scholars have illustrated the value struggles and the politics around offsetting tools and measurements (Robertson, 2012;Sullivan and Hannis, 2015), and offered compelling critiques of the economic rationality and quantitative frameworks underlying the offsetting ideology and the profit accumulation through offsetting (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have illustrated the value struggles and the politics around offsetting tools and measurements (Robertson, 2012;Sullivan and Hannis, 2015), and offered compelling critiques of the economic rationality and quantitative frameworks underlying the offsetting ideology and the profit accumulation through offsetting (e.g. Maron et al, 2015;Niner et al, 2017;Pawliczek and Sullivan, 2011;Robertson, 2004Robertson, , 2006. These are grounded in and further exacerbate what Dunlap and Sullivan (2019) call 'accumulation by alienation'.…”
Section: Introductionmentioning
confidence: 99%